Federal sex offender registration and notification act (SORNA) offenders: sexual versatility, criminal careers and supervision outcomes. Issue 4 (4th October 2021) - Drury, Alan J.; DeLisi, Matt; Elbert, Michael
Abstract : Purpose: Sex offender registration and notification act (SORNA) offenders are a source of scholarly study across the social, behavioral, forensic and legal sciences with the bulk of literature focusing on the legal standing and deterrent value of sexual offender registries. Less research focuses on the offending careers of current SORNA offenders relative to other types of sexual offenders whose current offense is not SORNA. The purpose of the current study is to examine this issue empirically. Design/methodology/approach: Using cross-sectional data from a census of male federal offenders who ever perpetrated a sexual offense from the central USA between 2016 and 2020, the current study used t -tests, logistic regression and negative binomial regression to compare current SORNA offenders to other federal correctional clients in terms of their lifetime offending history, sexual violence and compliance on federal supervision. Findings: Current SORNA offenders are significantly more severe and versatile in their sexual offending, have more extensive criminal careers and criminal justice system involvement, and exhibit significantly increased odds of revocation on supervised release despite controls for age, race and ethnicity. However, sensitivity models that specified the federal Post-Conviction Risk Assessment reduced the effects of SORNA status to non-significance in all models. Originality/value: SORNA offenders are potentially a significant offender group with evidence of both and given their versatile and specialized lifetime offending and noncompliance on federal supervision. However, current SORNA status is rendered spurious once a risk assessment is controlled suggesting more research is needed to evaluate whether sex offender registries posit greater crime control benefit.